Litter Controls Earthworm-Mediated Carbon and Nitrogen Transformations in Soil from Temperate Riparian Buffers - Maria Kernecker; Joann K. Whalen; Robert L. Bradley (Applied and Environmental Soil Science)
Nutrient cycling in riparian buffers is partly influenced by decomposition of crop, grass, and native tree species litter. Nonnative earthworms in riparian soils in southern Quebec are expected to speed the processes of litter decomposition and nitrogen (N) mineralization, increasing carbon (C) and N losses in gaseous forms or via leachate. A 5-month microcosm experiment evaluated the effect of Aporrectodea turgida on the decomposition of 3 litter types (deciduous leaves, reed canarygrass, and soybean stem residue). Earthworms increased CO2 and N2O losses from microcosms with soybean residue, by 112% and 670%, respectively, but reduced CO2 and N2O fluxes from microcosms with reed canarygrass by 120% and 220%, respectively. Litter type controlled the CO2 flux (soybean ≥ deciduous-mix litter = reed canarygrass > no litter) and the N2O flux (soybean ≥ no litter ≥ reed canarygrass > deciduous-mix litter). However, in the presence of earthworms, there was a slight increase in C and N gaseous losses of C and N relative to their losses via leachate, across litter treatments. We conclude that litter type determines the earthworm-mediated decomposition effect, highlighting the importance of vegetation management in controlling C and N losses from riparian buffers to the environment.